Mapping research ethics committees in Africa: Evidence of the growth of ethics review of health research in Africa. Issue 4 (3rd May 2017) - Mokgatla, Boitumelo; IJsselmuiden, Carel; Wassenaar, Doug; Kasule, Mary
Abstract: Health research initiatives worldwide are growing in scope and complexity, particularly as they move into the developing world. Expanding health research activity in low‐ and middle‐income countries has resulted in a commensurate rise in the need for sound ethical review structures and functions in the form of Research Ethics Committees (RECs). The urgent need for continued capacity development in Africa has necessitated research initiatives to identify existing capacity. This discussion paper describes the mapping of RECs in Africa through MARC (Mapping African Research Ethics Capacity) project, second phase (2012 to date) and discusses the findings. MARC provides a platform and tool on COHRED's Health Research HRWeb, which can be used by RECs and key stakeholders in health research in Africa to identify capacity, constraints and development needs.